Specific neurophysiological mechanisms underlie cognitive inflexibility in inflammatory bowel disease - Petruo, Vanessa A; Zeißig, Sebastian; Schmelz, Renate; Hampe, Jochen; Beste, Christian (Scientific reports, 2017)
Inflammatory bowel disease (IBD) is highly prevalent. While the pathophysiological mechanisms of IBD are increasingly understood, there is a lack of knowledge concerning cognitive dysfunctions in IBD. This is all the more the case concerning the underlying neurophysiological mechanisms. In the current study we focus on possible dysfunctions of cognitive flexibility (task switching) processes in IBD patients using a system neurophysiological approach combining event-related potential (ERP) recordings with source localization analyses. We show that there are task switching deficits (i.e. increased switch costs) in IBD patients. The neurophysiological data show that even though the pathophysiology of IBD is diverse and wide-spread, only specific cognitive subprocesses are altered: There was a selective dysfunction at the response selection level (N2 ERP) associated with functional alterations in the anterior cingulate cortex and the right inferior frontal gyrus. Attentional selection processes (N1 ERP), perceptual categorization processes (P1 ERP), or mechanisms related to the flexible implementation of task sets and related working memory processes (P3 ERP) do not contribute to cognitive inflexibility in IBD patients and were unchanged. It seems that pathophysiological processes in IBD strongly compromise cognitive-neurophysiological subprocesses related to fronto-striatal networks. These circuits may become overstrained in IBD when cognitive flexibility is required.
Keywords: idiopatické střevní záněty; evokované potenciály; Cognition; Analysis of Variance; Tumor Necrosis Factor-alpha; Evoked Potentials; mužské pohlaví; Adult; mladý dospělý; analýza rozptylu; TNF-alfa; kognice; Young Adult; ženské pohlaví; Reaction Time; Humans; reakční čas; Attention; pozornost; Neurophysiology; dospělí; Inflammatory Bowel Diseases; Female; neurofyziologie; lidé; Male